2009
DOI: 10.1016/j.febslet.2009.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen‐inducibleCaUGT1is involved in resistance response against TMV infection by controlling salicylic acid accumulation

Abstract: a b s t r a c tCapsicum annuum L. Bugang exhibits a hypersensitive response against Tobacco mosaic virus (TMV) P 0 infection. The C. annuum UDP-glucosyltransferase 1 (CaUGT1) gene was upregulated during resistance response to TMV and by salicylic acid, ethephon, methyl viologen, and sodium nitroprusside treatment. When the gene was downregulated by virus-induced gene silencing, a delayed HR was observed. In addition, free and total SA concentrations in the CaUGT1-downregulated hot pepper were decreased by 52% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…UDP-glucosyltransferase was another SA-associated up-regulated gene which is thought to be involved in the biosynthesis of SA [ 81 ]. A previously reported homologue in capsicum was also shown to be involved in tobacco mosaic virus resistance through controlling SA accumulation [ 57 ]. Auxin and ABA have also been implemented in plant-pathogen interactions [ 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…UDP-glucosyltransferase was another SA-associated up-regulated gene which is thought to be involved in the biosynthesis of SA [ 81 ]. A previously reported homologue in capsicum was also shown to be involved in tobacco mosaic virus resistance through controlling SA accumulation [ 57 ]. Auxin and ABA have also been implemented in plant-pathogen interactions [ 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with these observations, several factors that regulate the production and/or release of ILPs affect IIS and lifespan. These factors include the metabotropic GABA receptors or uncoupling proteins (UCPs) expressed in the IPCs (Fridell et al, 2009; Humphrey et al, 2009; Enell et al, 2010) and short neuropeptide F (sNPF) expressed in the CNS (Lee et al, 2008, 2009). In addition, downregulation of p53 in the IPCs extends lifespan by reducing ILP levels and inhibiting PI-3K activity in peripheral tissues (Bauer et al, 2007).…”
Section: Signaling Network: Intracellular Intercellular and Interomentioning
confidence: 99%
“…In tobacco plants carrying the N gene, SA GTase (SA UDP-glycosyltransferase) mRNA was induced by bacterial or viral pathogen (Lee and Raskin, 1999). Recent report showed that CaUGT1 is associated with disease resistance against Tobacco mosaic virus (TMV) in Capsicum annuum L. Bugang (Lee et al, 2009). Among the UGT super family in Arabidopsis, only group D members were known to be involved in disease resistance .…”
Section: Discussionmentioning
confidence: 99%